1995
DOI: 10.1111/j.1474-919x.1995.tb03226.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting nest site selection and nesting success in the Common Eider Somateria mollissima

Abstract: Nesting site selection and nesting success in Common Eiders Somateria mollissima were studied over a 3‐year period (1991–1993) in the Mast River delta (58o24'N, 94o24'W), 40 km east of Churchill, Manitoba, Canada. Eiders preferentially nested on islands that had incubating Lesser Snow Geese Anser caerulescens caerulescens on them; this effect was also seen between years on the same islands. Eiders which nested on islands with geese had a reduced chance of having eggs taken by predators during egg‐laying and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Finally, suggested that extensive ice can form bridges between mainland areas and breeding islands, providing increased access for the mammalian predators such as Arctic fox, polar bear. For example, Robertson (1995b) found that islands further from mainland areas were less likely to be visited by foxes. In each of the above scenarios, eiders might beneWt by delaying nesting until ice conditions permit better access to food or reduce access by predators.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, suggested that extensive ice can form bridges between mainland areas and breeding islands, providing increased access for the mammalian predators such as Arctic fox, polar bear. For example, Robertson (1995b) found that islands further from mainland areas were less likely to be visited by foxes. In each of the above scenarios, eiders might beneWt by delaying nesting until ice conditions permit better access to food or reduce access by predators.…”
Section: Discussionmentioning
confidence: 96%
“…It is likely that eiders and gulls are drawn to similar nesting islands with certain environmental characteristics such as being offshore to avoid mammalian predators (Robertson 1995;Wyman et al 2014). In Labrador, eiders show a strong preference for islands that do not trap ice in spring, and so would not be connected to mainland areas and accessible to mammalian predators (Chaulk et al 2007;Chaulk and Mahoney 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, gulls would also be attracted to nest on these islands for the same protection from mammals. A relationship between gull and eider abundance could simply be a function of island size (e.g., Robertson 1995), where a restricted number of nesting territories are possible on smaller islands. However, we found no relationship between island size and eider or gull abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid follicular growth takes about 9 days in common eiders (Robertson 1995); nearly 2 weeks can separate the recruitment of the Wrst follicle and the ovulation of the last one in a four-egg clutch. Due to ice cover, early nesting eiders at our study site are likely forced to feed about 20 km oV the nesting island while forming their Wrst egg.…”
Section: Intra-clutch Variationmentioning
confidence: 99%